The Effect of Contextual Learning in Civic Education on Studentsâ Civic Skills - Komalasari, Kokom (EDUCARE, 2012)
ABSTRACT: The development of Civic Education cannot be isolated from globalization tendency that influences the studentsâ life. However, the recent fact in Indonesia is that learning is still dominated by conventional system. Thus, the implementation of learning oriented to âcontextualized multiple intelligencesâ concept is still far away from its wish. This study aimed to describe the effect of contextual learning in Civic Education on studentsâ civic skills. The process of study used quantitative approach with survey method. The population of study was Junior High School students in West Java, Indonesia, taught by Civic Education teachers who had followed Competence-Based Integrated Training. The total sample was 1,004 students based on cluster, proportional, and systematic random sampling. The result of study showed that contextual learning in West Java Junior High Schools belonged to average category. The civic skills of Junior High School students in West Java were belonged to high category. There was significant effect of contextual learning on studentsâ civic skills, which was shown with correlation by 0.48 and contribution by 23%. Therefore, teachers should apply contextual learning, the government should develop effective training system to improve the teachersâ competence in contextual learning and teacher education institutionÂ should develop innovation of learning model involving school. KEY WORDS: Contextual learning, civic education, studentsâ civic skills, thinking skill and participative skill, and good and democratic citizens.Â About the Author: Dr. Hj. Kokom Komalasari is a Lecturer at the Department of Civic Education, Faculty of Social Studies Education UPI (Indonesia University of Education), Jalan Dr. Setiabudhi No.229 Bandung 40154, West Java, Indonesia. She can be reached at: komsari36@yahoo.co.idHow to cite this article? Komalasari, Kokom. (2012). âThe Effect of Contextual Learning in Civic Education on Studentsâ Civic Skillsâ in EDUCARE: International Journal for Educational Studies, Vol.4(2) February, pp.179-190. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 15, 2011); Revised (January 20, 2012); and Published (February 17, 2012).